SOSIALISASI PENGGUNAAN APLIKASI KESEHATAN SEBAGAI ALAT PEMANTAUAN DAN PENDIDIKAN TENTANG STUNTING DAN PENGGUNAAN OBAT YANG TEPAT - Binuko, Raafika Studiviani Dwi; Joni Maulindar (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
The issues of stunting and inappropriate drug use pose serious challenges to public health, including in Indonesia. Stunting, often caused by early-life nutritional deficiencies, has long-term impacts on children's health and development. Meanwhile, improper drug use can lead to harmful side effects and drug resistance. Hence, a socialization activity was conducted using the method of Socialization of Health Application Usage as a Tool for Monitoring and Education on Stunting and Proper Drug Use. This approach combines educational, practical, and social support elements to ensure its effectiveness. Through educational sessions, participants gain a deep understanding of the importance of proper drug use and the negative effects of improper drug use. Hands-on sessions using health applications enable participants to apply their knowledge in monitoring children's growth and understanding stunting indicators. Relevant exercises in real-life situations are also provided to hone participants' skills in using the applications in their daily lives. Evaluation reveals positive changes in participants' understanding and attitudes, as well as increased confidence in facing health challenges. Pre-test and post-test results indicate a significant improvement in participants' understanding of the subject matter and practical skills, from 36.5% to 81.2% in understanding the material and from 47.1% to 87.5% in understanding practical aspects. This underscores the effectiveness of the socialization approach in enhancing participants' knowledge and skills related to stunting and proper drug use through health applications.